EXPERIMENTAL AND QUANTUM CHEMICAL STUDIES OF 5-FLUOROISATIN-3-(N-CYCLOHEXYLTHIOSEMICARBAZONE) AND ITS METAL COMPLEXES - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2012)
Zn(II) and Ni(II) complexes of 5-fluoroisatin-3-[-(N-cyclohexylthiosemicarbazone)] (H2FIC) have been prepared and characterized structurally by means of elemental analyses, FTIR, electronic, and H-1 NMR spectra. The theoretical wavenumbers, IR intensities, and molecular parameters have been calculated by the ab-initio Hartree-Fock (HF) method with the LanL2DZ basis set. The theoretical wavenumbers show a good agreement with experimental data. The bond lengths, bond angles, the highest occupied molecular orbital energy (E-HOMO), the lowest unoccupied molecular orbital energy (E-LUMO), the energy gap between E-HOMO and E-LUMO (Delta EHOMO-LUMO), dipole moment, and charges on the atoms of H2FIC as monomer form were studied by the density functional theory/Becke-3-Lee-Yang-Parr (DFT/B3LYP) and ab-initio HF methods using 6-31G(d, p) basis set. The trimeric possible structure of H2FIC was also investigated using HF method. The observed IR wavenumbers of the H2FIC were analyzed in the light of the computed vibrational spectra of its monomer and trimer forms. Supplemental materials are available for this article. Go to the publisher's online edition of Phosphorus, Sulfur, and Silicon and the Related Elements to view the free supplemental file.
Keywords: 5-fluoroisatin-3-thiosemicarbazone; zinc(II); nickel(II); DFT; HF calculations; FTIR spectra; ISATIN; ZINC(II); THIOSEMICARBAZONES; COPPER(II)